Modification of the existing maximum residue levels and setting of import tolerances for thiabendazole in various crops. (11th May 2021) - ; Anastassiadou, Maria; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta España S.A. submitted a request to the competent national authority in Spain to modify the existing maximum residue levels (MRLs) in citrus fruits, bananas and witloofs. Additionally, Syngenta Crop Protection AG submitted two applications to Spain to set import tolerances in mangoes and in sweet potatoes. The data submitted in support of the requests were found to be sufficient to derive MRL proposals for the commodities under evaluation and for commodities of animal origin. Adequate analytical methods for enforcement are available to control the residues of thiabendazole in the commodities under consideration and in animal matrices at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of thiabendazole according to the reported agricultural practices is unlikely to present a risk to consumer health.